THE EFFECTIVENESS OF USING VOCABULARY TREES AS A TECHNIQUE IN TEACHING VOCABULARY AT ELEMENTARY SCHOOL - Binta Nugroho Septiyantono (Universitas PGRI Semarang, 2013)
The topic of the research is the effectiveness of vocabulary trees as a teaching aid to develop the students’ vocabulary mastery. The Objective to investigate whether there is any significant difference in the vocabulary mastery between teaching vocabulary trees and using conventional method. In order to achieve the objective of this research, the writer designed an experimental research. The subject used in the research was 60 students of the fifth grade of SD Negeri Bendungan Semarang; 30 students acted as the experimental group to be taught vocabulary using vocabulary trees and the other 30 students as the control group to be taught vocabulary using conventional method. Before the experiment was conducted, a pre-test was given to both groups. A post test was given after the experiment was done. The test consisted of 25 items of multiple choice types. The test items were first tried out to check the validity, reliability, difficulty level and discriminating power. The result shows that there are significant differences in mean score between control group and experimental group. Mean score of the pre test of the experimental group is 50.53 while that of the control group is 48.33. Thus, the difference between the two means is 2.46. In the post test, the mean score of the experimental group is 81.07 and of the control group is 69.73. Thus, the difference between the two means is 11.34. The result of the t-test based on the pre-test is 0.86, while the result on the post test is 4.52 and the critical value 2.000. Based on the result above, it can be concluded that teaching vocabulary using vocabulary trees resulted in a better learning achievement. The t-value of the post test is higher than the critical value, which means that the students got better understanding when they used vocabulary trees as a technique to improve students’ vocabulary mastery than when they used conventional method. In conclusion, vocabulary is effective and applicable enough as a learning aid to be used in developing students’ vocabulary.